2020
DOI: 10.3390/catal10121377
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Combustion of Propane over Pt-Mo/ZSM-5 Catalyst: The Promotional Effects of Molybdenum

Abstract: To improve propane combustion activity and illustrate the promotional effects of molybdenum doping, Pt-Mo/ZSM-5 catalysts with different Mo amounts were prepared by the co-impregnation method. XRD, Raman, H2-TPR, NH3-TPD, in situ DRIFTs, XPS and other characterizations were performed. The results indicated that the concentration of Pt0 in Pt/ZSM-5 catalyst increased after the doping of Mo and the content of Pt0 had a positive correlation with the reaction turnover frequency value. The propane combustion activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In addition, the BE of Mo shifted higher with increasing Mo loading, which was related to the interactions between the metal and support. 41…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…In addition, the BE of Mo shifted higher with increasing Mo loading, which was related to the interactions between the metal and support. 41…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…Enriching the electron density of the Pt surface through electronic metal–support interaction, ,,, variations in work functions of metal and support, as well as distinct reduction procedures , can facilitate oxygen activation and reactant adsorption, thus accelerating oxidation rates. Previous work has demonstrated that secondary promoters can adjust the electronic state of Pt, thereby affecting catalytic performance. For instance, d-block transition metal oxides like VO x , , WO 3 , ,, and MoO 3 ,, can modulate the electron density of neighboring Pt when placed in proximity, demonstrating promotional effects such as tailoring adsorption behavior and enhancing ability to oxidize VOCs. However, a fundamental understanding of the underlying principles governing these “electro-tuning” phenomena, encompassing both the spatial and electronic structures of Pt and the secondary metal oxides, and how these relate to reactant adsorption and activation, is still largely missing.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have focused on strategies to improve supported Pt nanocatalysts, including metal–support interactions, promoters, and structural adjustments. Tailoring Pt’s electronic properties to enhance its interactions with reactants like VOCs and oxygen is of particular interest. Enriching the electron density of the Pt surface through electronic metal–support interaction, ,,, variations in work functions of metal and support, as well as distinct reduction procedures , can facilitate oxygen activation and reactant adsorption, thus accelerating oxidation rates.…”
Section: Introductionmentioning
confidence: 99%